A case study about reducing delayed discharge from hospital : exploring how East Ayrshire Health and Social Care Partnership (HSCP) ensures that people are safely and legally discharged from hospital to home, or a homely setting, as soon as they are medically fit.: exploring how East Ayrshire Health and Social Care Partnership (HSCP) ensures that people are safely and legally discharged from hospital to home, or a homely setting, as soon as they are medically fit. (May 2019) - Unknown
No abstract available